Prevalence and determinants of pre-term deliveries in the University of Ilorin Teaching Hospital, Ilorin, Nigeria - O. A. Mokuolu; B. M. Suleiman; O. O. Adesiyun; A. Adeniyi (MDPI AG, 2010)
In Nigeria, over 900,000 children under the age of five years die every year. Early neonatal death is responsible for a little over 20% of these deaths. Prematurity remains a significant cause of these early neonatal deaths. In some series, it is reported to be responsible for 60-70% of these deaths. This study aimed to determine the prevalence and determinants of pre-term deliveries at the University of Ilorin Teaching Hospital, Ilorin. This was a prospective cohort study conducted over a 9-month period at the University of Ilorin Teaching Hospital. Records of deliveries and data on maternal socio-biological and antenatal variables were collected during this period in order to determine the prevalence and determinants of pre-term deliveries. Out of the 2,489 deliveries that took place over a 9-month period, there were 293 pre-terms, giving a pre-term delivery rate of 120 per 1,000 deliveries. Of the total deliveries, 1,522 singleton deliveries that satisfied inclusion criteria were recruited; 185 of them were pre-term deliveries giving a case:control ratio of 1:7. Significant determinants of pre-term delivery identified were previous pre-term delivery (P=0.001; OR=3.55; 95% CI=1.71-7.30), antepartum hemorrhage (P=0.000; OR=8.95; 95%CI=4.06-19.78), premature rupture of the membranes (P=0.000; OR=6.48; 95%CI=4.33-9.67), maternal urinary tract infection (P=0.006; OR=5.89; 95%CI=1.16-27.57), pregnancy induced hypertension (P=0.007; OR=3.23; 95%CI=2.09-4.99), type of labor (P=0.000; OR=6.44; 95%CI=4.42-9.38) and booking status (P=0.000; OR=4.67; 95%CI=3.33-6.56). The prevalence of pre-term delivery was 120 per 1,000 live births. Factors significantly associated with pre-term delivery were low socio-economic class, previous pre-term delivery, antepartum hemorrhage, premature rupture of fetal membranes, urinary tract infection, pregnancy induced hypertension, induced labor, and booking elsewhere outside the teaching hospital.